2007
DOI: 10.2337/dc06-1190
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Metabolic Syndrome Components to Cognition in Older Individuals

Abstract: OBJECTIVE -Recent evidence suggests that the metabolic syndrome and inflammation affect cognitive decline in old age and that they reinforce each other. However, it is not known what the roles of the individual components of the metabolic syndrome on cognition are. RESULTS -Of the sample, 36.3% had metabolic syndrome. Metabolic syndrome was significantly associated with all cognitive measures (P Ͻ 0.05). Of the individual components, hyperglycemia was most strongly and significantly associated with cognitive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

28
177
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(214 citation statements)
references
References 27 publications
28
177
4
5
Order By: Relevance
“…[9][10][11][12][13][14][15][16] A particularly notable aspect of the present study is that MetS-related differences in BOLD response to a demanding cognitive challenge were detected in participants without clinically significant cognitive dysfunction. As evidenced by the widely used exercise stress test, dysfunction in physiologic systems is more likely to manifest when the system is stressed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16] A particularly notable aspect of the present study is that MetS-related differences in BOLD response to a demanding cognitive challenge were detected in participants without clinically significant cognitive dysfunction. As evidenced by the widely used exercise stress test, dysfunction in physiologic systems is more likely to manifest when the system is stressed.…”
Section: Discussionmentioning
confidence: 77%
“…8 Growing evidence suggests that MetS is also harmful to cognition and that the cluster may have predictive value for cognitive decline over and above that of its individual components. [9][10][11][12][13][14][15][16] Older patients with MetS score lower on cognitive tests than agematched healthy adults, particularly on measures of processing speed and executive functioning, 17 cognitive domains that are associated with vascular cognitive impairment. Several studies have shown that middle-aged individuals with MetS are at higher risk of developing dementia in late life, 18 yet accurate prediction of individual cognitive trajectories is difficult due to the low sensitivity of paper-and-pencil screening tests to subtle changes in intellectual functioning.…”
mentioning
confidence: 99%
“…And this non-association remained regardless of the presence of ApoE e4 allele. However, previous studies reported that there was a significant association between MS and cognitive decline in the elderly (Dik et al, 2007;Komulainen et al, 2007;Van den Berg et al, 2007;Yaffe et al, 2007). It is possible that due to difference of the research design, different results may be obtained.…”
Section: Discussionmentioning
confidence: 45%
“…Another possibility is that there was a significant interaction between the MS and inflammation on cognition. The MS was negatively associated with cognition in subjects with high inflammation whereas an association was absent in subjects with low inflammation (Dik et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
“…Hyperglycemia, a marker for insulin resistance and the main feature of MetS, may have direct negative effects on cognition, whereas such direct effects have not been discovered for the other components [23]. Another probable mechanism is the effect of the elevated inflammation often seen in patients with MetS [7,23] Markers of inflammation have been associated with an increased risk of cognitive decline and developing dementia [7]. Inflammation may also be viewed as part of MetS.…”
Section: Discussionmentioning
confidence: 99%